CORRUPTION IN GOVERNMENT: KNOWLEDGE AND OPPORTUNITIES FOR FUTURE RESEARCH - Merawati, Luh Komang; I Ketut Yadnyana; Ni Made Dwi Ratnadi; Putu Agus Ardiana (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2025)
Corruption and efforts to reduce it through the implementation of good governance have emerged as prominent topics in recent years. However, there are still diverse yet unorganized viewpoints on the concept of defining and measuring corruption. Particularly, the concept of corruption in government necessitates a more comprehensive synthesis to provide a structured overview of the existing literature and pinpoint opportunities for further advancement in this field of study. Nonetheless, previous research has made efforts in making observations to guide future research in a holistic manner. To address this issue, a systematic literature review (SLR) of 44 articles addressing good governance, including transparency, accountability, participation, and their relationship with corruption, provided a comprehensive overview synthesizing current knowledge in this domain. Specifically, it reviews the state of knowledge of the reviewed literature, identifies potential research areas, and provides recommendations to broaden avenues for future research.